PENGARUH CUSTOMER SERVICE, MERCHANDISE ASSORTMENTS, PERCEIVED PRICE, DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN DI MATAHARI DEPARTEMENT STORE SEMARANG - Helmy Bagus Saputra; Alimuddin Rizal Riva’i (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2016)
In the global era, development of the retail industry in Indonesia is so fast, the development of the retail industry in Indonesia has increased over the last 10 years, both retail supermarkets and retail non-self-service, with the rapid development of the retail business, then competition in the field of retail marketing or retail are increasingly increased. This study aimed to analyze the effect of customer service, merchandise assortments, perceived price, and store atmosphere on purchasing decisions in Matahari Department Store Semarang. The population is all consumers who ever bought at Matahari Department Store Semarang. Samples in this study were 100 respondents to the sampling technique used was purposive sampling technique. Analysis tool used to test the hypothesis in this study is t-test and f-test. In this study using a test instrument to test the validity by factor analysis (KMO) and reliable test. The results showed that customer service, merchandise assortments, perceived price, and store atmosphere had positive and significant effect on purchasing decisions. Keywords: Customer service, merchandising assortments, Perceived price, store atmosphere, and the purchase decision